Prevalence, risk factors, impact on milk yield, and farmers’ awareness of lameness and claw lesions in dairy cows in Selangor, Malaysia - Babatunde, Sadiq Mohammed (2018)
Lameness is an important production limiting disease in the dairy industry globally. Despite the recent development of dairy production in Selangor and Malaysia, studies on lameness occurrence and claw health are limited. The objectives of the study reported in this thesis were: i) To determine the prevalence of lameness and claw lesions; ii) To identify the cow level risk factors for lameness; iii) To determine the incidence of lameness, claw lesions and association with floor types and their impact on milk yield; and 4) To assess the level of awareness of dairy farmers in Selangor lameness occurrence, associated risk factors and claw health management practices. A cross-sectional study involving 251 lactating cows from eight farms was conducted to estimate the prevalence of lameness, distribution of claw lesions and associated risk factors. The cows were assessed by locomotion scoring (LS), claw examination and animal-based risk factors. Pearson chi-square was used to compare the prevalence estimates from all the studied farms, as well as the association between proportion of lame cows and those with claw lesions. A binary logistic regression with backward elimination method was applied to investigate the association between independent variables and prevalence of lameness and claw lesions. The prevalence of lameness in cows was 19.1% (48/251, range: 10-33.3%) while 31.1% (78/251) of cows had claw lesions (range: 22.4-40%). Of all claw lesions (n=161) recorded, the occurrence of overgrown claw (OC), sole lesions (SL), white line disease (WLD), and digital dermatitis (DD) were 24.8, 21.7, 13.0 and 9.9%, respectively. Claw lesions were recorded in 87.5% (42/48) of the lame cows with highest being those affected with SL (54.2%; 19/35) and WLD (61.9%; 13/21). Lameness was associated with early lactation (odds ratio, OR = 3.3; 95% Confidence interval, CI 1.5, 7.3), injured hocks (OR = 4.8; 95% CI 1.4, 16.6) and dirty leg (OR=2.6; 95% CI 1.04, 6.5) and OC (OR = 2.0, 95% CI 1.4, 4.9) whereas presence of claw lesions was associated with dirty leg (OR= 4.9; 95% CI 2.3, 10.5) and OC (OR= 2.68; 95% CI 1.3, 5.3). The incidence of lameness, claw lesions and association with floor types and impact on milk yield was also assessed through a longitudinal study conducted from October, 2016 to July, 2017 involving four farms (120 cows total) with 60 cows each from two farm types, using either rubber mats (RM) or concrete floor (CF). Data on LS, animal characteristics and milk yield were collected monthly, and claw assessment was done twice, at the beginning and end of study. Incidence of lameness and claw lesions and their associations with floor types and cow level factors were analysed using binary logistic regression. Association between milk yield and other independent variables was done using a univariate analysis of variance (ANOVA). Overall, the cumulative incidence of lameness in the study population was 24.2% (29/120). The incidence rate (IR) of lameness in cows on CF was 43.6% (18/41.25 cow-years) and 24.6% (11/44.6 cow-years) in cows on RM. Lameness was associated with very dirty leg (OR = 6.6, 95% CI 1.7, 26.5) and OC (OR = 8.4, 95% CI 2.0, 34.5). Moderate body condition score (BCS) was a protective factor for lameness (OR=0.3, 95% CI 0.1, 0.9). A total of 34 claw lesions were recorded in 24 cows on CF while 29 claw lesions were observed in 20 cows on RM. However, the difference was not significant (P>0.05). Amongst the 44 cows affected with claw lesions, the highest were those with SL (31.7%), WLD (15.6%), DD (14.3%) and toe ulcers (TU), interdigital hyperplasia (IH), and swollen coronet (SC) (8% each). Claw lesions were present in 93% (n=27/29) of all lame cows and mostly located in the hind claws. Incidence of claw lesions was associated with very dirty leg (OR = 4.4, 95% CI 1.3-14.8) and OC (OR = 4.4, 95% CI 1.5, 12.9). Mean monthly milk yield was higher (P < 0.05) in cows at higher parity compared with primiparous cows, while lower (P < 0.05) in cows with injured hock compared with those with normal hock condition. Based on the structured questionnaire survey distributed to 120 dairy farmers, to assess their perception on impact of lameness, risk factors and practices related to claw health management, a response rate of 68.3% (82/120) was recorded. Farmers’ responses (agree or not agree) were not different regarding lameness being an important health problem in dairy cows and its negative impact on reproductive performance. A higher proportion (P = 0.01) of farmers (77%; 63/82) were aware of the factors considered to influence lameness occurrence at herd level, while comparable proportions (P = 0.91) were aware (51%; 42/82) and unaware (49%; 40/82) of the cow level factors. Awareness of the risk factors was common (P < 0.05) among farmers with higher education qualification and years of farming experience. Fifty percent of the farmers (41/82) were unaware of the welfare assessment practices related to claw health. Only 29% (24/82) of the farmers practiced claw trimming. The results suggest low awareness of lameness occurrence among the surveyed dairy farmers.